RETRACTED: A Path Towards Green Revolution: How do Environmental Technologies, Political Risk, and Environmental Taxes Influence Green Energy Consumption? - Peng, Gao; Meng, Fanchen; Ahmed, Zahoor; Oláh, Judit; Harsányi, Endre (Frontiers in Environmental Science, 2022)
Enhancing green energy consumption is the most important strategy to achieve environmental goals and control global temperature rise. Unquestionably, political intuitions make decisions for developing environmental technologies and imposing environmental taxes for phasing out fossil fuels and achieving energy transitions. Therefore, this study explores the role of environmental technologies, political risk, and environmental taxes in green energy consumption considering the potential impacts of population density and economic growth in G7 countries. Second-generation tests are applied for analyzing the long-run equilibrium connection and stationarity features. Finally, the CuP-FM and CuP-BC estimators are applied for assessing long-run linkage and Dumitrescu-Hurlin causal test is applied to reveal causal flow among variables. The estimates uncovered that enhancing environmental technologies and environmental taxes upsurges the consumption of green energy. Reducing political risk in G7 countries also boosts green energy consumption. Economic growth is evidenced to stimulate the consumption of green energy, while population density limits the consumption of green energy. Moreover, environmental technologies and political risk Granger cause green energy utilization, while a feedback relationship exists between environmental taxes and green energy usage. Based on the results, strategies to boost green energy consumption are discussed.